I Don’t Want to Say Goodbye : A Man’s Journey Through Grief - Siok Ping, Voon (2021)
Grieving is hard. Grieving during Covid-19 pandemic is even harder. The purpose of this case study is to illustrate the grieving journey of a 40 years-old Malaysian Chinese man who experienced physical and mental complications after the death of his loved one from cancer. The client was presented with several somatic symptoms such as backache, stomach upset, shoulder pain, neck and abdominal discomfort since first onset in October 2020. Hehad been seeking various medical consultations including undergone colonoscopy and Oesophagus Duodenoscopy Procedure (OGDS), but to no avail. Client identified his physical symptoms with his late partner and adopted his late partner sleeping posture to feel better. He reported symptoms of major depressive disorder (MDD) with significant loss of appetite and weight, loss of interest, sadness, sense of worthlessness and hopelessness. After the death of his loved one in March last year he found it hard to overcome the devastating feelings related to the loss and reported feeling loss of directionin his life. His work performance has dropped drastically since then. Of particular concern,client was susceptible to unresolved and complicated grief. He was not able to attend the funeral due to the pandemic, leaving him a great deal of unsettled feelings. Client was in relationship with the deceased for 13 years, he showed great closeness and high dependencyin the relationship with the decedent. He reported strong sense of guilt to forget her. Theseincreased the complexities of grief and caused the grieving process to be derailed. The therapist created a supportive, empathic relationship with client and helped him to face hisloss gradually. The therapeutic alliance drew out client’s emotions and feelings in relationto his loved one’s death. By taking into the broader sense of how grief manifests itself and individual differences in the grief experience, the custom-tailoring of intervention integrated different modalities and techniques to facilitate healthy grieving process, these include pharmacotherapy and grief focused therapy. Treatment was initiated with antidepressants. Instead of gaining closure or trying to say goodbye, the goal of therapy fostered a constructive continuing bond with the deceased person, this was accomplished through honouring the deceased loved one, remembering the good times, setting up an internal dialogue with the lost loved one, continuing to think of that person on a regular basis and imagining the person's reactions to current life events. The outcome of the intervention revealed that client demonstrated marked improvement with reduced depressive symptoms. After attending four sessions, he began to accept the reality of his loss. He managed to allow himself to grieve and cry if needed, adjust to a new reality in which the deceased is no longerpresent and moved forward positively in his life. He became able to talk about his deceased loved one without becoming overly upset. While the client has made significant progress in his grieving process and resuming his own life, he still occasionally experiences physical discomfort. This case study highlighted the importance of conceptualizing the client as “the self-in-context”, understanding the biopsychosocial impact of the death of a loved one has emphasized the use of self in therapyon identifying and treating people at risk for physical andpsychological issues as a result of their significant loss. Establishing the emphatic relationshipwith client, providing solidemotional support and recognizing the resilience in griever are essential to providing effective therapy to client with unresolved loss. Facing the loss of lovedone can be difficultbut healthy ways to cope with loss are possible.